CAROTENOIDS AS NATURAL COLORANT : A REVIEW - Fany Dwi Wahyuni; Ila Maratush Shalihah; Winda Nurtiana (University of Sultan Ageng Tirtayasa, 2020)
Color is quality attribute that is usually used by consumer as first assessment to choose the food product. However, food processing is one of process which can degrade the food’s color, so the colorant is usually added. On this era, consumer tend to choose food products that have functional benefit. One of natural colorant which has it is carotenoids. Carotenoids gives red, orange, and yellowish. Carotenoids are divided into two groups, carotene and xanthophyll. Carotene consists of α-carotene, β-carotene, γ-carotene, and lycopene. Meanwhile, xanthophyll consists of β-cryptoxanthin, lutein, zeaxanthin, astaxanthin, fucoxanthin, and peridinin. This pigment is lipophilic so it can dissolve in oils and organics solvents and is quite resistant to heating, however it can be very easily degraded in acidic, light, and oxygen condition. Beside act as colorant, this pigment can act as antioxidant and provitamin A. The source of carotenoids is widely spread in flowers, fruits, tubers, leaves, and fruit peels. Extraction of this pigment can be done in three ways, there are maceration extraction, supercritical fluid extraction, and enzymatic extraction.